Bioterrorism preparedness, attack and response - Blair, John D. 1944-; Fottler, Myron D.; Zapanta, Albert C. (Emerald, 2004)
A volume that provides a view into the world of Bioterrorism and how it could affect the healthcare system of the United States. It will lead the reader along a journey that shows ramifications to health, politics, and everyday common actions. The book starts out by informing the reader of biological agents and then leads into how organizations and the government should respond in the case that such agents are unleashed. A full understanding of bioterrorism preparedness and response cannot be achieved effectively by considering these phenomena in a vacuum nor informed only by the bioterrorism literature in its current form. The authors identify the key factors that make up the essential pieces of bioterrorism preparedness, attack and response. This volume puts what is normally thought of bioterrorism preparedness issues in their equally important security and terrorist strategy contexts. Here, the editors have sought to bring experts insights on as many of the interlinking factors as possible into one volume. This thematic volumes objectives are to facilitate the readers understanding of the new reality that creates certainty in the uncertainty facing them in the future. It provides knowledge of Bioterrorism and advances skills of preparedness. It shows ramifications of a terrorist attack and gives the reader a view of possible terrorist attacks. It presents a look into security and terrorist strategy.
Keywords: Business & Economics -- Management.; Medical -- Hospital Administration & Care.; Social issues & processes.; Bioterrorism.; elektronické knihy; electronic books